Getting square pegs out through round holes: A survey of Australian and New Zealand Gynaecologists regarding specimen retrieval. (12th October 2022) - Bryant‐Smith, Alison; Lowe, Jessica; Lam, Alan
Abstract : Aims: To evaluate morcellation practices among Fellows of the Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG). Materials and methods: RANZCOG Fellows were invited to complete an online survey. This anonymous, cross‐sectional survey consisted of 29 questions regarding demographics and morcellation practices. Results: Four hundred and thirty eight (19.04%) of 2300 RANZCOG Fellows responded, and of these 258 (11.22%) completed the entire survey; analysis was undertaken on data from the latter respondents. Respondents were broadly representative of all RANZCOG Fellows regarding gender, age, and location. Of the respondents, 53.10% considered themselves advanced laparoscopic surgeons. Of respondents who had worked as gynaecology consultants prior to 2014, 39.39% used uncontained power morcellation prior to 2014, compared to 17.58% since (a decrease of 44.63%). The most common reasons for utilising uncontained power morcellation less often were the 2014 Food and Drug Administration warnings (40.31%), risk of adverse outcomes (33.72%), and recommendations from colleges such as RANZCOG (27.13%). When undertaking an operation that required specimen extraction, the most common methods used were: employing an open approach from the get‐go (utilised by respondents in 31.01% of such cases); contained manual morcellation (28.90%); and conversion to intra‐operative laparotomy (10.10%). Conclusions: There has been a strong trend away from uncontained power morcellation since 2014, with a 36.00% increase in clinicians who never use uncontained power morcellation, and an 80.65% decrease in clinicians who always use this method of specimen extraction. The most common reason cited for employing uncontained power morcellation less often was the 2014 Food and Drug Administration's warnings.